The Effect of Enzyme and Probiotics Mixture in Drinking Water with Protein Level Differences on Body Weights, Feed Conversion and Production index on Broiler - Sufiriyanto, Sufiriyanto; Indraji, Mohandas (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2001)
This experiment was study of the enzyme and probiotic in drinking water mixture was affected on body weight, feed conversion and production index in broiler. This experiment was carried out using 144 broilers, started at one day old and finished at 42 days of age, divided into 4 type treatment of three different level of protein. Experimental method was based on randomized complete design with twelve treatments, if differently, followed by orthogonal polynomial. Type 1 (unit ABC) was treated with mixture of drinking water and amylase, protease and probiotic at day 3rd through 5th, day 14th , day 21st, day 28th and 35th ; type 2 (unit DEF) was treated at day 7th ,17th, 27th and 37th ; type 3 (unit GHI) was treated day 21th , day 28th and 35th ; type 4 (unit JKL) without treatment (control). The level of protein for group I of unit ADGJ was 19% of starter feed and 16% of finisher feed. The level of protein for group II unit BEHK was 21 %of starter feed and 18% finisher feed. The variable used in body weight, feed conversion, production index at the 5th and 6th weeks of age. Result indicated that the body weight optimum was 1483.33 gram at the 5th weeks of age and 1868,89 gram, feed conversion 1, 826 and production index 279,31 at the 6th weeks of age. These findings were observed in the group of chicken given drinking, water amylase, protease and probiotic mixed with at day 3rd trough 5th , day 14th , day 21st , day 28th and day 35th ; The level of protein was 23% of starter feed and 21% of finisher feed. The mixture of enzyme and probiotic in drinking water was concluded to improve in body weight, feed conversion and production index of broiler. (Animal Production 3(1): 26-30 (2001)Key Words: Broiler, enzyme, probiotic, body weight, feed conversion, production index.